The phytoplankton of Guanabara Bay, Brazil: I. historical account of its biodiversity - Villac, Maria Célia; Tenenbaum, Denise Rivera (Biota Neotropica, 2010)
This is a historical account of the biodiversity of phytoplankton in Guanabara Bay, Brazil. It is based on 57 publications that refer to sampling carried out between 1913 and 2004. The publications included are those with direct microscopic identification. Although 80% of the studies focus on ecological issues that tend to mention only the most abundant species, 24 publications provide comprehensive check-lists at the species level, especially of taxa > 20 μm. The inventory of species includes, to date, 308 taxa among 199 diatoms, 90 dinoflagellates, 9 cyanobacteria, 5 euglenophyceans, 1 chlorophycean, 1 prasinophycean, 1 silicoflagellate, and 2 ebriids. The most conspicuous species were the dinoflagellate Scrippsiella trochoidea and diatoms from the Skeletonema costatum complex. The first was the theme of the very first publication in the area (Faria 1914) that reported on its bloom associated with the mass mortality of fish due to oxygen depletion; it is still often found in high abundances (10(6) cell.L-1) in more protected areas. The second was long considered in the literature as a cosmopolitan and opportunistic species, until the recent discovery of cryptic species within the genus; taxonomic re-evaluation of local populations is, therefore, needed. Besides these two species, only other 25 species stood out in terms of frequency of occurrence and widespread distribution in the Bay, some known to be implicated in harmful blooms elsewhere. The biodiversity of dinoflagellates, especially within the Gymnodiniales, and that of other unidentified flagellates (Haptophyceae, Cryptophyceae, Prasinophyceae, Raphidophyceae) is largely underestimated because of the use of fixatives that distort/destroy diagnostic characters. From the initial inventory of 124 taxa published in 1917 and the subsequent additions in species numbers, one can have a false perception that the phytoplankton biodiversity has increased throughout the years, despite the overall increase in eutrophication observed in Guanabara Bay. The reason for this may be twofold: 1) it is an artifact caused by our progressively improving technical capability to detect and identify species and 2) the possible effects of eutrophication could be better perceived when the community structure is evaluated, that is, when space-time variations in the abundances of the populations (rather than just number of species) are also taken into account.